RETORIKA USTADZ ABDUL SOMAD - Rozita, Rozita; Charlina, Charlina; Sinaga, Mangatur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research discusses the technique of rhetoric of Ustadz Abdul Somad. The data in this study was obtained from Ustadz Abdul Somad's lecture